Strategic Human Resource Management and Organizational Justice in the Indonesian Police: Psychological Safety as a Mediator Toward Institutional Integrity - Simaremare, Rissan; Meiske Claudia; Rini Rahmawati (International Journal of Economics, Business and Innovation Research, 2025)
Abstract This study investigates the influence of Strategic Human Resource Management (SHRM) and Organizational Justice on Institutional Integrity within the Indonesian National Police, with Psychological Safety acting as a mediating variable. A cross-sectional survey was conducted with 100 police personnel from various units, and the data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM).The results show that SHRM and Organizational Justice significantly enhance both Psychological Safety and Institutional Integrity. Specifically, SHRM had a stronger direct impact on Psychological Safety (β = 0.585) and Institutional Integrity (β = 0.333) compared to Organizational Justice (β = 0.464 and β = 0.233, respectively). Psychological Safety also showed a significant positive effect on Institutional Integrity (β = 0.410), confirming its role as a mediating mechanism. Theoretically, this study contributes to public sector ethics by integrating psychological safety into models of institutional integrity. Practically, it highlights the importance of value-based HR strategies and justice-driven managerial practices in fostering ethical resilience in hierarchical public organizations.